COPART Risk Score, Endothelial Dysfunction, and Arterial Hypertension are Independent Risk Factors for Mortality in Claudicants. Issue 2 (August 2016) - Hackl, G.; Jud, P.; Avian, A.; Gary, T.; Deutschmann, H.; Seinost, G.; Brodmann, M.; Hafner, F.
Abstract : Objective: The COPART risk score consists of six variables to assess the prognosis of PAOD patients. The flow mediated dilation (FMD) quantifies endothelial function. The aim of this study was to evaluate the mortality prediction of these two variables in a long-term observation of claudicants. Methods: 184 consecutive claudicants were included in a prospective observational study over a median observation period of 7.9 (IQR 7.2–8.7) years. The endothelial function was assessed on the day of study inclusion using brachial FMD. Results: Three groups were assigned according to the COPART risk score: low risk (LR), n = 72 (39%); medium risk (MR), n = 59 (32%); and high risk (HR), n = 53 (29%). Overall survival rates differed among COPART risk score groups ( p < .001, 5 year survival: LR group 83% [95% CI 74–92%]; MR group 73% [95% CI 62–84%]; HR group 57% [95% CI 43–70%]). Survivors had a significantly better median FMD than non-survivors (4.1% [IQR 1.2–6.4] vs. 1.3% [IQR 0.0–4.2]; p < .001). Also the FMD differed significantly among the three COPART risk groups (LR 4.0% [IQR 1.2–6.3], MR 2.3% [IQR 0.0–6.3], HR 1.7% [IQR 0.0–3.6]; p = .033). Finally, independent predictors for disease specific survival were COPART risk score ( p = .033; MR group [HR 1.6], 95% CI 0.7–3.6; HR group [HR 2.7], 95% CI 1.2–5.8), FMD ( p = .004; FMD ≤2.5 vs. >2.5, HR 2.6, 95% CI 1.4–4.9), and arterial hypertension ( p = .039; HR 3.5, 95% CI 1.1–11.3). Conclusions: COPART risk score, FMD, and arterial hypertension are independent long-term mortality predictors in this group of claudicants. The best mortality assessment is provided by including all three predictors.